PENERAPAN MODEL COOPERATIVE LEARNING TIPE STAD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BAHASA ARAB SISWA KELAS XI IPS-2 SMA MUHAMMADIYAH 1 KALIREJO LAMPUNG TENGAH TAHUN 2011 : PENERAPAN MODEL COOPERATIVE LEARNING TIPE STAD - Langgeng Sutopo; Muhammad Ari Wibowo (An Naba, 2018)
The decreasing of student learning outcomes in Arabic subjects are influenced by several factors, one of which is the lack of student activity in the learning process, besides the application of learning is still conventional by the teacher concerned. So that students are less active and fed up with Arabic lessons, this results in a low average grade of student learning outcomes. One solution and attraction for the effectiveness of increasing learning activities is the cooperative learning model or cooperative learning model of Student Teams Achievement Divisions (STAD) type. This study aims to (1) describe student’s learning activities in Arabic subjects through the STAD type of cooperative learning model, (2) describe student-learning outcomes in Arabic subjects through the STAD type of cooperative learning model. The research subject is class XI IPS-2 Muhammadiyah 1 Kalirejo High School, Central Lampung, with 37 students. This study uses qualitative and quantitative data as a measurement tool to improve student-learning outcomes of the class. Based on the analysis results the researchers concluded that the class had increased activity and learning outcomes in each cycle. The increase in learning activities is higher than the increase in learning outcomes; this is because students feel excited to be a better study group than other study groups even though their abilities vary in one group.